ANALYSIS OF THE COMPETITIVE POSITION OF INDONESIAN PEPPER IN THE INTERNATIONAL MARKET - Lilis Imamah Ichdayati; Dewi Rohma Wati; Iffa Aulia (Syarif Hidayatullah State Islamic University Jakarta, 2021)
The world pepper price, which tends to decline, and the increasing production and quality of pepper from competing countries, have also made it difficult for Indonesian pepper to increase its export volume and value. This study aims to, 1) analyze the structure of the Indonesian pepper market in the international market, 2) analyze the potential competitiveness of Indonesian pepper in terms of comparative and competitive advantages in the international market, 3) analyze the specialization position of the Indonesian pepper trade in the international market. The data used is data for the period 2010-2019.The results of this study are known that the market structure of Indonesian pepper commodities in the United States and Germany is monopolistic. Meanwhile, in the other three main export destination countries, namely Vietnam, India, and Singapore, the market structure of Indonesian pepper commodities is an oligopoly. Based on the average value of RCA, Indonesian pepper commodities have a comparative advantage in five main export destination countries, namely Vietnam, India, the United States, Germany, and Singapore. The market position of pepper commodities in the two main export destination countries, namely Vietnam and India, is in the falling star position. Meanwhile, in the other three main destination countries of Indonesian pepper, the average value is in a Retreat position. The conclusions of this study show that the market structure of Indonesian pepper commodities in the United States and Germany is monopolistic, while in other countries such as Vietnam, India, and Singapore the market structure is oligopoly. Indonesian pepper commodities have a comparative advantage in five destination countries with an average RCA value of more than 1. The market position of pepper commodities in Vietnam and India is the falling star position, while in the United States, Germany, and Singapore, the average value is in the Retreat position. Indonesian pepper commodities in 4 main export destination countries, namely Vietnam, the United States, Germany, and Singapore are at the maturity stage, while in India it is at the growth stage.